Handbook of the Unknowable - Armstrong, Rachel 1966-; Gullström-Hughes, Rolf; Gangvik, Espen (Trondheim TEKS, 2016)
This Handbook of the Unknowable came about as a conversation between Espen Gangvik, Director Trondheim Biennale, Norway, Rachel Armstrong, Professor of Experimental Architecture, Newcastle University, UK, and Rolf Hughes, Head of Research and Professor of Artistic Research at Stockholm University of the Arts, Sweden. The discussion related to how the arts and space communities may explore productive research conversations in a festival setting. The idea that the publication itself could be viewed in dialogue with the Biennale programme came about as an alternative reading of the festival theme ‘It’s Nice to be in Orbit’ for Meta.Morf 2016. Conceptually, the publication represents a journey from the present understanding and engagement with ‘space’ towards an uncertain, yet optimistic future ‘among the stars’. The reader is invited to imagine the near-term prospect of human space habitation. If it is the case that we relate to the extraordinary terrains that make up our solar system in an almost mundane, technological, colonizing mindset today, then the work presented here – with its reverent insistence on enchantment – is offered as a necessary counterpoint. We will not imagine the unimaginable unless some brave souls start to help us do so. Such a ‘handbook’ – the editors have deliberately chosen the name of such a pragmatic or practical genre in order to smash it against the mysterious concept of ‘unknowability’, thereby creating an alternative vision to that articulated so suavely in countless techno-utopian space reports – invites discovery while simultaneously declaring the impossibility of any notion of resolution in such hypercomplex, alien and vast spaces. In other words space remains both familiar and exotic. We are confronted not only with the strangeness of matter but also with the irreducibility of ourselves. Space, in short, can be said to be queer in every sense of the term. This means our acquired habits and existing knowledge sets are unlikely to get us very far. We’ll need to find ways to think against (and outside) ourselves. Here the arts can be an important ally.
Contributions by Ester Armstrong, Rachel Armstrong, Andrew Ballantyne, Krists Ernstsons, Paul Gilster, Rolf Hughes, Sarah Jane Pell & Frederik de Wilde
Published in connection with Meta.Morf 2016 - Nice to be in orbit! Biennale for art and technology, Trondheim, Norway
Keywords: 21st Century (2001-2100); Astronomy; Artistic research; Science; Technology